2020
DOI: 10.5115/acb.19.051
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic sympathetic ganglia cells of the ventral root of the spinal cord: an anatomical study

Abstract: The sympathetic trunk ganglia contain the cell bodies of neurons. However, some patients who undergo sympathectomy can develop compensatory hyperhidrosis. To evaluate for ectopic pathways, the present anatomical study was performed. Ten adult cadavers underwent dissection of the spinal canal and removal of randomly selected ventral roots, which were submitted for histological analysis. Random ventral root samples were taken from cervical, thoracic, and lumbosacral regions in each specimen. Each histological se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Catecholaminergic cell bodies are found not only in ganglia, but also in the cranial nerves themselves, such as the (lingual branch of the) glossopharyngeal nerve [ 27 , 79 ], the cervical [ 80 ] and laryngeal branches of the vagus nerve [ 81 , 82 ], and the cranial root of the hypoglossal nerve [ 83 ]. In addition, catecholaminergic cell bodies are found in both the ventral and dorsal spinal nerve roots [ 84 – 99 ], and in the hypogastric and the (“parasympathetic”) pelvic splanchnic nerves [ 16 , 17 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catecholaminergic cell bodies are found not only in ganglia, but also in the cranial nerves themselves, such as the (lingual branch of the) glossopharyngeal nerve [ 27 , 79 ], the cervical [ 80 ] and laryngeal branches of the vagus nerve [ 81 , 82 ], and the cranial root of the hypoglossal nerve [ 83 ]. In addition, catecholaminergic cell bodies are found in both the ventral and dorsal spinal nerve roots [ 84 – 99 ], and in the hypogastric and the (“parasympathetic”) pelvic splanchnic nerves [ 16 , 17 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Many of these proximal cell bodies subsequently nest in the sympathetic trunk. Other proximal locations, however, include the spinal nerve roots [ 84 – 99 ], dorsal root ganglia [ 28 , 31 , 48 59 , 95 ], and white and gray rami communicantes [ 85 – 91 , 95 – 98 , 106 – 111 ]. In the pelvic area, usually characterized as parasympathetic, these proximal locations of ganglionic cells also exist, both in sacral nerve roots [ 84 , 93 , 99 ] and in the proximal part of the pelvic splanchnic nerves [ 16 , 17 , 93 , 112 – 114 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…There are 2-6 pairs of lumbar sympathetic ganglia, most of which are located at the level of the corresponding vertebral body or between the upper and lower vertebral bodies, and are usually located in the lateral nucleus of the lateral column of the spinal gray matter at the third position of the lumbar spine. The main areas of innervation include the lower limbs, buttocks, and the ischium [20][21][22].…”
Section: The Anatomical Basis Of Sympathetic Nervementioning
confidence: 99%
“…The sympathetic system involves the districts of the tentorium and tongue and the cervical roots. It has been shown that in the ventral roots of all the medullary segments and in part in the axonic fibers, there are sympathetic cells identical to the cells that constitute the sympathetic ganglia of the corresponding anatomical chain [48]. We don't know the real function of these sympathetic cells.…”
Section: Pharyngeal Plexus and Ansa Cervicalismentioning
confidence: 99%